Sustainability and the Circular Economy through the Eyes of Students: A Comparative Analysis among Bulgaria, North Macedonia, Slovenia and Croatia - Kostadinova, Irina; Todorova, Ana; Ruskova, Svilena; Tomovska Misoska, Ana; Letonja, Marina; Tomljanović, Marko (European Journal of Sustainable Development, 2025)
Higher education institutions are the catalyst for building tomorrow’s leaders who will take responsibility for addressing environmental issues and shaping a more sustainable future. Along with learning the principles of the circular economy and sustainability, students build the skills and knowledge needed to take up leadership positions in a variety of fields, including business, politics and non-governmental organizations. This article analyzes the understanding of issues of sustainability, circular and green economy through the eyes of business-oriented students from four European countries: Bulgaria, North Macedonia, Slovenia and Croatia. An international team of scientists researches the attitudes and expectations of students from different bachelor’s and master’s programs with the aim of both improving their knowledge, skills and competencies related to circular and green economy and sustainability, as well as upgrading and enriching educational programs and processes. The research identified gaps in the educational process along with identified good practices implemented by specific partner organizations. Interrelationships were sought between the final results and the current geopolitical situation of the respective country in the context of its membership or not in the European Union. The study analyzed the content of various disciplines, focusing specifically on research areas such as the circular and green economy and sustainability. The findings aim to enhance curricula in fields like corporate social responsibility, economics, marketing, and related areas. Keywords: sustainability, circular economy, green economy, education